Outcomes of Endoscopic Biliary Drainage in Postsurgical Anatomy Using Endoscopic Ultrasound and Enteroscopy: A Comparative Study - Jamwal, Kapil Dev; Sharma, Atul; Padhan, Rajesh Kumar; Sharma, Manoj Kumar (Journal of Digestive Endoscopy, 2023)
Objectives Biliary obstruction is a common problem encountered in postsurgical anatomy, which may lead to serious complications if not treated promptly. Endoscopic drainage is a minimally invasive and effective treatment option for such patients. However, the optimal route of endoscopic drainage, either SBE-ERCP (single-balloon enteroscopy with endoscopic retrograde cholangiopancreatography) or EUS-BD (endoscopic ultrasound-guided bile duct drainage), remains controversial. In this study, we aim to evaluate the feasibility and outcomes of endoscopic drainage using these two techniques in postsurgical biliary obstruction over a period of 7 years.Materials and Methods We conducted a retrospective study of patients who underwent endoscopic drainage for postsurgical biliary obstruction using SBE-ERCP or EUS-BD techniques between 2015 and 2022. The demographic details, clinical presentation, procedure duration, number of sessions required, technical success, complications, and change of procedure from SBE-ERCP to EUS-BD or vice versa were recorded.Results Seventy-five patients, predominantly females with a mean age of 48 years, underwent endoscopic drainage. Forty-eight patients underwent SBE drainage and 27 patients underwent EUS-HG (EUS-guided hepaticogastrostomy). The mean duration of procedure (44 vs. 77 minutes), number of complications (4 vs. 5), technical success rate (93.5 vs. 85%), change of procedure (0 vs. 3), and number of sessions (1.1 vs. 1.8) were significantly less in the EUS-HG as compared to SBE-ERCP.Conclusions Endoscopic biliary drainage is feasible, safe, and effective in postsurgical biliary anatomy but requires high technical expertise. The study proposes an algorithm that can be applied in such group of patients to determine the route for choosing the drainage procedure. This requires further validation with a large prospective cohort.
Keywords: cholangitis; pneumobilia; hepaticojejunostomy; ERCP; biliary drainage